Timing of Atlantic cod (Gadus morhua L.) seasonal migrations in the southern Gulf of St Lawrence: interannual variability and proximate control - Comeau, L. A.; Campana, S. E.; Chouinard, G. A. (ICES Journal of Marine Science, 2002)
The objective of this study was to identify likely proximate cues to the seasonal migrations of cod, Gadus morhua L., in the southern Gulf of St Lawrence. We computed a migration timing index across several years using commercial fishery (1970–1992) and sentinel survey (1995–1999) catch rate data, and closely monitored the seasonal changes in temperature, dissolved oxygen, food intake, and energy stores between 1995 and 1998. The inter-year variability in the timing of the seasonal migrations was relatively low (s.d. = 8 d for spring migration, 10 d for autumn migration), suggesting that photoperiod was involved in the control mechanism of migration. However, other factors were also implicated in the control mechanism, given that cod initiated the autumn migration progressively earlier in the late 1980s and 1990s. At the onset of the autumn migration, dissolved oxygen concentrations were above levels known to induce avoidance behaviour in this species, and food resources were considered to be relatively abundant. Similarly, cod did not initiate the autumn migration at a specific temperature or following a particular temperature regime experienced during summer. However, cross correlation function analysis indicated that a widespread cooling of near bottom waters preceded the mid-1980s shift in migration timing by one to two years, suggesting that the cooling event was linked in some way to the change in migration dates. Other correlations showed that the earlier migrations coincided with older cod becoming more abundant and smaller in size, and also with their principal fish prey (herring and capelin) increasing in number. These results suggest that older cod played a key role in launching the early autumn migrations. One plausible interpretation is that their decline in body size and lipid-rich diets led to a rapid build up of energy reserves over summer grounds, and thus to an earlier readiness to engage in the autumn migration. We discuss the potential impact of earlier departures on stock productivity.